2015
DOI: 10.1002/ajmg.a.37336
|View full text |Cite
|
Sign up to set email alerts
|

Two further patients with the 1q24 deletion syndrome expand the phenotype: A possible role for the miR199–214 cluster in the skeletal features of the condition

Abstract: Submicroscopic deletions within chromosome 1q24q25 are associated with a syndromic phenotype of short stature, brachydactyly, learning difficulties, and facial dysmorphism. The critical region for the deletion phenotype has previously been narrowed to a 1.9 Mb segment containing 13 genes. We describe two further patients with 1q24 microdeletions and the skeletal phenotype, the first of whom has normal intellect, whereas the second has only mild learning impairment. The deletion in the first patient is very sma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
16
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 20 publications
4
16
0
Order By: Relevance
“…With regards to the skeletal phenotype, our cases provide further evidence supporting the significance of DNM3 and/or miR199–214 in the skeletal features, as suggested by Ashraf et al (). There has been no published evidence to suggest a role for DMN3 in skeletal development.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…With regards to the skeletal phenotype, our cases provide further evidence supporting the significance of DNM3 and/or miR199–214 in the skeletal features, as suggested by Ashraf et al (). There has been no published evidence to suggest a role for DMN3 in skeletal development.…”
Section: Discussionsupporting
confidence: 88%
“…However, mouse studies support a potential role for miRNA199–214 in skeletal development (Watanabe et al, ). Functional studies have also indicated involvement of both miR199 and miR214 in bone formation (Ashraf et al, ). There is emerging evidence to suggest that miR214 is involved in regulating the Wnt/B catenin signaling pathway in the development of human osteosarcoma.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[59][60][61][62][63][64] Recently, Ashraf et al reported two additional patients with microdeletions in 1q24q25 that display similar skeletal abnormalities as reported previously (i.e., short stature, brachydactyly, and facial dysmorphism). 65 The deletion mutation in one of these patients narrowed down the critical region causing these skeletal defects to that encoding dynamin-3 (DNM3) and two miRNAs located within intron 14 of this gene (miR-199a and miR-214). Interestingly, a study by Watanabe et al showed skeletal defects in mice devoid of the long non-coding RNA, Dnm3os, an antisense transcript in intron 14 of Dnm3 that harbors both miR-199a and miR-214.…”
Section: Mirnas Regulating Skeletal Development and Homeostasis-evidementioning
confidence: 99%